Contraception and Sexsual Activity as Factor Influenced Leucorrhea - sari priyanti; Agustin Dwi Syalfina (Universitas Airlangga, 2017)
ABSTRACT Cervical cancer was non communicable desease that worries the public and causes an increase mortality in women. One of the first sign causes of cervical cancer is occourrence of Leucorrhoe. The incidence of Leucorrhoe in women Indonesia by 90% of which >75% of women experience once of leucorrhoe and experience ≥ 2 times by 25%. Leucorrhoe should not be considered an ordinary thing because can be caused to itchy on genetalia, pain during sexsual, infection  can be caused odema on genetalia, hot like burned on vagina even the impact if not treated promptly will caused infertility and cancer. Aims of study was to analyze factors of influenced on Leucorrhoe incident. Design of study was cross sectional study. Population was women of childbearing age who use contraceptives in the karang jeruk village, Jatirejo sub district, Mojokerto district in March of 2017. Sample in this study was 33 people. Data analyze with logistic regresion. Result of study showed contraceptive and sexsual activity has significant influenced with leucorrhoe (PR = 10.000; 95% CI= 1,732-57,722 dan PR=8,750; 95% CI=1,466-52,232). Suggestion: should be married and have first sexual intercourse for the first time at the age of  ≥ 20 years, limit the number of children not more than 2 as the greater the number of children the greater the risk of Leucorrhoe, and not using hormonal contraception for a along time that more than 2 years.   Keywords: contraceptive,sexsual activity, leucorrhoe